Purchase order for supply of HT cable for substation for BRACU new campus building at holding no. Kha 224, Merul Badda, Dhaka-1212 - Brac University (Brac University, 2023)
This purchase order has been made between Brac University and BBS Cables Ltd. for the supply of HT cable for substation for Brac University new campus project.